Gully erosion assessment in mountainous regions: a RUSLE-based methodology for the Central Peruvian Andes - Paucar-Y-Montenegro, C.; Rosas, M.A.; Arancibia, A. (Taylor and Francis Ltd., 2026)
Soil erosion is a significant global threat, with gully erosion forming deep hillside channels that substantially contribute to sediment yield. While erosion is often assessed using models like the Revised Universal Soil Loss Equation (RUSLE), its limitation to only consider surface erosion, avoiding severe erosion processes, led us to develop RUSLEad, an adapted version for gully erosion. The method integrates the Topographic Wetness Index (TWI) and a region-specific sediment delivery ratio in its formulation and includes generalized likelihood uncertainty estimation for model validation. Our pilot study is a basin of 13 km2 located in the Central Peruvian Andes. There, we collected detailed topographic and soil data. Chosen for its cost-effectiveness and data accessibility, RUSLEad produced erosion maps and average sediment yield estimates, and identified erosion hotspots. This method, applicable to similar terrain elsewhere, supports Peru’s Climate Change Strategy 2050 by informing gully control and contributing to prioritizing potential remediation efforts.
Keywords: Gully erosion; Erosion; Hydrology (agriculture); Vegetation (pathology); Water erosion; https://purl.org/pe-repo/ocde/ford#1.05.06